2013
DOI: 10.1016/j.sjopt.2013.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Lacrimal glands in cystic fibrosis

Abstract: Cystic fibrosis is a systemic disease involving defective mucus secretion in different parts of the body resulting in a wide range of systemic complications. We are presenting the histology of the lacrimal gland from a 25 year old male with cystic fibrosis using light microscopy. To the best of our knowledge this is the first report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Further studies are needed in order to clarify potential alterations in LG morphology later in life. In a case report by Alghadyan et al 37 histopathologic examinations of LGs of CF patient who died of pulmonary complications revealed clogged small duct lumens and subsequent degeneration of acinar cells.…”
Section: Discussionmentioning
confidence: 97%
“…Further studies are needed in order to clarify potential alterations in LG morphology later in life. In a case report by Alghadyan et al 37 histopathologic examinations of LGs of CF patient who died of pulmonary complications revealed clogged small duct lumens and subsequent degeneration of acinar cells.…”
Section: Discussionmentioning
confidence: 97%
“…Pharmaceutics 2021, 13, x 7 of 16 cluding xerophthalmia, papilledema, and retinal hemorrhages [51]. Joshi et al [52] reported the first case of newly diagnosed CF-related liver disease in a teenage boy presenting symptoms of night blindness secondary to vitamin A deficiency.…”
Section: Ocular Disorders Derived From Cystic Fibrosis Diseasementioning
confidence: 99%
“…Currently, eye manifestations of CF are less well known; however, mounting evidence suggests that ocular disorders in CF are a serious problem. A number of ocular disorders derived from CF have been reported, including xerophthalmia, papilledema, and retinal hemorrhages [ 51 ]. Joshi et al [ 52 ] reported the first case of newly diagnosed CF-related liver disease in a teenage boy presenting symptoms of night blindness secondary to vitamin A deficiency.…”
Section: Ocular Disorders Derived From Cystic Fibrosis Diseasementioning
confidence: 99%
“…The analyte concentrations in tears and biomedical component characteristics for human eyes are confined within normal ranges [39][40][41][42][43][44][45][46][47] in healthy individuals. When the analyte concentration is beyond the specific range (Table I), this leads to related diseases [48][49][50][51][52]. Therefore, multiple biomarkers in tear fluids may be used for disease screening.…”
Section: Introductionmentioning
confidence: 99%